The LRRC8/VRAC anion channel facilitates myogenic differentiation of murine myoblasts by promoting membrane hyperpolarization - Chen, Lingye (J Biol Chem, 2019)
Skeletal muscle myoblast differentiation involves elaborate signaling networks, including the activity of various ion channels and transporters. Several K(+) and Ca(2+) channels have been shown to affect myogenesis, but little is known about roles of Cl(−) channels in the associated processes. Here, we report that the leucine-rich repeat containing family 8 (LRRC8)/volume-regulated anion channel (VRAC) promotes mouse myoblast differentiation. All LRRC8 subunits of heteromeric VRAC were expressed during myotube formation of murine C2C12 myoblasts. Pharmacological VRAC inhibitors, siRNA-mediated knockdown of the essential VRAC subunit LRRC8A, or VRAC activity-suppressing overexpression of LRRC8A effectively reduced the expression of the myogenic transcription factor myogenin and suppressed myoblast fusion while not affecting myoblast proliferation. We found that inhibiting VRAC impairs plasma membrane hyperpolarization early during differentiation. At later times (more than 6 h after inducing differentiation), VRAC inhibition no longer suppressed myoblast differentiation, suggesting that VRAC acts upstream of K(+) channel activation. Consequently, VRAC inhibition prevented the increase of intracellular steady-state Ca(2+) levels that normally occurs during myogenesis. Our results may explain the mechanism for the thinning of skeletal muscle bundles observed in LRRC8A-deficient mice and highlight the importance of the LRRC8/VRAC anion channel in cell differentiation.